Relationship between landing strategy and patellar tendinopathy in volleyball. Issue 7 (15th January 2007) - Bisseling, Rob W; Hof, At L; Bredeweg, Steef W; Zwerver, Johannes; Mulder, Theo
Abstract : Objective: The aetiology of patellar tendinopathy (jumper's knee) remains unclear. To see whether landing strategy might be a risk factor for the development of this injury, this study examined whether landing dynamics from drop jumps differed among healthy volleyball players (CON) and volleyball players with a jumper's knee. The patients with jumper's knee were divided into an asymptomatic group with a previous jumper's knee (PJK) and a symptomatic group with a recent jumper's knee (RJK). Methods: Inverse dynamics analyses were used to estimate lower extremity joint dynamics from 30, 50 and 70 cm drop jumps in the three groups (CON, n = 8; PJK, n = 7; RJK, n = 9). A univariate repeated measures analysis of variance was used to compare the different landing techniques. Results: Data analysis of the landing dynamics revealed that PJK showed higher knee angular velocities (p<0.01), and higher ankle plantar flexion moment loading rate (p<0.01). Furthermore, strong tendencies of higher loading rate of vertical ground reaction force (p = 0.05) and higher knee extensor moment loading rate (p = 0.08) were found compared with CON. Higher values for peak knee moment, peak knee power and knee work (all p<0.01) were found for CON compared with RJK. The comparison of the two jumper's knee groups yielded higher knee angular velocities (p<0.01), together with higher ankle plantar flexion and knee extensor moment loading rate (p<0.01 and p<0.05, respectively). Conclusion: Where RJK used a landing technique to avoid high patellar tendon loading, PJK used a stiffer landing strategy, which may be a risk factor in the development of patellar tendinopathy.